Cat Scabies Prevalence at Animal Health Center Pemalang - Nila Qudsiyati; Aulia Khirqah; Abdul Muntolip; Dwi Priyowidodo; Soedarmanto Indarjulianto; Raden Wisnu Nurcahyo (Jurnal Sain Veteriner, 2023)
Scabies in cats is an infectious skin disease caused by the mite Sarcoptes scabiei that attacks the stratum corneum layer of the cat's skin at all ages and is zoonotic. The purpose of this study is to determine the prevalence of scabies using cat patient data from the Pemalang Animal Health Center from May 13th to July 15th, 2022, as well as morphological information of S. scabiei. The scabies diagnosis method employs two stages, namely the examination of clinical and laboratory symptoms. Purposive sampling was used to select laboratory examination samples. Cats with clinical scabies use the skin scraping technique, which involves scraping the skin in the area around the lesion, placing it on an object glass, dripping with 10% KOH, covering it with a cover glass, and examining it under a 400x microscope. The prevalence of scabies in cat patients at the Pemalang Health Center was 33.19%, and S. scabiei was found on the legs of cat patients.